2017
DOI: 10.1038/s41598-017-01480-2
|View full text |Cite|
|
Sign up to set email alerts
|

Kanglaite sensitizes colorectal cancer cells to Taxol via NF-κΒ inhibition and connexin 43 upregulation

Abstract: Taxol, a first-line anti-tumour drug, has low effectiveness against colorectal cancer. Combination with other agents is an effective strategy to enhance Taxol cytotoxicity. Kanglaite injection is an extract from Coix lacryma-jobi seed and is usually combined with other agents to treat cancer. The aim of this study was to investigate the treatment effect of Taxol combined with Kanglaite on colorectal cancer cell lines. Kanglaite pretreatment followed by Taxol treatment was found to show the best synergism among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Cx43 is the most widely expressed connexin in a variety of tissues and is a structural component of GJ . Some reports have shown that paclitaxel inhibits GJ function and Cx43 expression to decrease cytotoxicity of itself . Cx43 as well as other GJ molecules, such as Cx32 and Cx26, has been shown to inhibit primary tumor cell progression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cx43 is the most widely expressed connexin in a variety of tissues and is a structural component of GJ . Some reports have shown that paclitaxel inhibits GJ function and Cx43 expression to decrease cytotoxicity of itself . Cx43 as well as other GJ molecules, such as Cx32 and Cx26, has been shown to inhibit primary tumor cell progression.…”
Section: Resultsmentioning
confidence: 99%
“…Gap junction (GJ) function was examined using the "Parachute" dyecoupling assay as described by Wang et al 6 Cells were seeded in six-well plates and grown to 80%-100% confluency. CM-Dil and Calcein-AM were used to determine GJ function.…”
Section: "Parachute" Dye-coupling Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…p-Akt also upregulates (17) or downregulates (18) the phosphorylation of Cx43 (p-Cx43), depending on the cell type. Phosphorylation is a necessary step for Cx43 to form gap junctions (19), which sensitizes cancer cells to many antitumor drugs (20). However, the nature of the interaction between p-Cx43 and p-Akt in colorectal cancer cells, and whether this interaction affects the cytotoxicity of cetuximab, are still unknown.…”
Section: Introductionmentioning
confidence: 99%